Estimation of efficiency of information support of operators of computerized systems maintaining air traffic - Неделько, С. Н.; Неделько, В. Н. (Proceedings of National Aviation University (archive), 1999)
Determined are the peculiarities of intellectual computerized systems of air traffic maintenance. Proposed is classification of information operators support